Encoding of Whisker Vibration by Rat Barrel Cortex Neurons: Implications for Texture Discrimination - Arabzadeh, Ehsan (J Neurosci, 2003)
Rats, using their whiskers, have excellent capabilities in texture discrimination. What is the representation of texture in rat somatosensory cortex? We hypothesize that as rats “whisk” over a surface, the spatial frequency of a grooved or pebbled texture is converted to a temporal frequency of whisker vibration. Surface features such as groove depth or grain size modulate the amplitude of this vibration. Validation of the hypothesis depends on showing that vibration parameters have distinct neuronal representations in cortex. To test this, we delivered sinusoidal vibrations to the whisker shaft and analyzed cortical neuronal activity. Seven amplitudes and seven frequencies were combined to construct 49 stimuli while recording activity through a 10 × 10 microelectrode array inserted into the middle layers of barrel cortex. We find that cortical neurons do not explicitly encode vibration frequency (f) or amplitude (A) by any coding measure (average spike counts over different time windows, spike timing patterns in the peristimulus time histograms or in autocorrelograms). Instead, neurons explicitly encode the product of frequency and amplitude, which is proportional to the mean speed of the vibration. The quantity Af is an invariant because neuronal response encodes this feature independently of the values of the individual terms A and f. This was true across a wide time scale of firing rate measurements, from 5 to 500 msec. We conclude that vibration kinetics are rapidly and reliably encoded in the firing rate of cortical ensembles. Therefore, the cortical representation of vibration speed could underlie texture discrimination.